ANALISIS KESULITAN MEMBACA DAN MENULIS SISWA KELAS I SD MUHAMMADIYAH 6 SURAKARTA - Surani (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2024)
This research is a descriptive research. The subjects in this research were all 1st grade students at SD Muhammadiyah 6 Surakarta, totaling 22 students. This research aims to determine the factors that influence difficulties in reading and writing. Data collection was obtained from observation, interviews and documentation. The research results showed that some of the students were fluent and could read and write, but there were 3 children who still had difficulty reading and writing. Difficulty reading and writing is influenced by several factors, namely environmental factors which include family or parents, assistance and supervision, student interest and motivation and the school environment. The teacher's strategy for overcoming reading and writing difficulties is by providing attention, practice, guidance by the teacher and also collaboration between teachers and parents so that the reading and writing process runs smoothly. Keywords: Analysis, Reading and Writing, Elementary School